ANTERIOR RECURRENT EPISTAXIS FROM KIESSELBACH’S AREA - Skitarelić, Neven; Čulina, Ņeljko; Bačić, Ivan; Skitarelić, Natańa (European Scientific Journal, ESJ, 2014)
Vascular diseases are a major threat to human health nowadays. Hypertension, cardiovascular disease and varicose vain disease including hemorrhoids, are now increasingly recognized as inflammatory diseases. The role of inflammation cytokines in the pathogenesis of these diseases is very important. The lamina propria in the nasal mucosa is rich in blood vessels and humoral mediators. Recurrent epistaxis from Kiesselbach‘s area syndrome (REKAS) was first mentioned as early as 1985. It has been found that 90% of patients suffering from recurrent epistaxis from Kiesselbach area syndrome simultaneously suffered from hemorrhoids. Clinical observations suggest a possible mutual pathophysiologic relationship between Kiesselbach‘s and anorectal venous plexus. This relationship is also suggested in the reverse direction: significantly more than two thirds of primarily hemorrhoidal patients (83.01%) showed simultaneous vascular dilatations within their Kiesselbach plexuses, but none of these patients had ever have recurrent nose bleeds. There is one more thing they did not have (contrary to REKAS group) - anterior septal deformity. Furthermore, REKAS and hemorrhoidal disease, despite being different clinical entities, frequently appear in the primarily REKAS patients or their closest relatives (more than 90% out of all!). At the same time, all of REKAS patients did have a certain degree of the anterior septal deformity, which primarily hemorrhoidal patients did not have at all. Therefore we consider that Kiesselbach‘s vascular plexus in the Little‘s area of the nasal septum belongs to the same group as anorectal venous plexus does (others of this group are brain, esophagus, and lower leg venous system). We also consider that the anterior septal deformity is a crucial factor for the onset of the inflammation of the nasal vestibule skin (vestibulitis nasi), while vestibulitis nasi precipitates the onset of typical recurrent nose bleeds from the Kiesselbach‘s plexus.